Szkolnictwo wyznaniowe i nauczanie religii w świetle osobistych zapisków prymasa Stefana Wyszyńskiego z 1961 roku - Wiśniewska, Monika (Biuletyn Historii Wychowania, 2019)
This article presents educational issues in the Polish People’s Republic as presented in Primate Stefan Wyszyński’s personal notes (called pro memoria) from 1961. The major source of the study is a Stefan Wyszyński manuscript stored in the Archdiocese Archive in Gniezno. In the first part of the study, an outline of research into education in the Polish People’s Republic is presented, together with methodological issues. The second part is devoted to a brief summary of education against the ideological pressure exerted by the Communist authorities by 1961. The third part presents the characteristics of the source representing the basis of the study. The fourth part presents (in the light of Primate Wyszyński’s notes) the act on the development of education and upbringing from 1961, care and education institutions of the Roman Catholic Church, kindergartens managed by nuns and parishes, religious education, church secondary education, religious instruction, lower seminaries, higher seminaries, tertiary education and academic religious leadership.